Question
upstudy study bank question image url

Function Point \[ y=\cos (3 x) \quad\left(\frac{\pi}{4},-\frac{\sqrt{2}}{2}\right) \] (a) Find an equation of the tangent line to the graph of the function at the given polnt. (Let \( x \) be the Independent variable and \( y \) be the dependent variable.) \( y=\cos (3 x) \)

Ask by Welch Gross. in the United States
Feb 26,2025

Upstudy AI Solution

Tutor-Verified Answer

Answer

The equation of the tangent line to the graph of \( y = \cos(3x) \) at the point \( \left(\frac{\pi}{4}, -\frac{\sqrt{2}}{2}\right) \) is: \[ y = -\frac{3\sqrt{2}}{2} \left(x - \frac{\pi}{4}\right) - \frac{\sqrt{2}}{2} \]

Solution

We start with the function:   y = cos(3x). Step 1. Find the derivative of y with respect to x to determine the slope of the tangent line.   y′ = d/dx [cos(3x)]. Using the chain rule:   y′ = -sin(3x) · 3 = -3 sin(3x). Step 2. Evaluate the derivative at x = π/4.   y′(π/4) = -3 sin(3(π/4)) = -3 sin(3π/4). Recall that sin(3π/4) = √2/2. Therefore:   y′(π/4) = -3(√2/2) = -(3√2)/2. This is the slope (m) of the tangent line at the point. Step 3. Write the equation of the tangent line using the point-slope form:   y - y₁ = m (x - x₁), where (x₁, y₁) = (π/4, -√2/2) and m = -(3√2)/2. Substitute these values:   y - (-√2/2) = -(3√2)/2 (x - π/4)   y + (√2)/2 = -(3√2)/2 (x - π/4). This is the equation of the tangent line. You can leave the answer in point-slope form or simplify further. For example, solving for y, we have:   y = -(3√2)/2 (x - π/4) - (√2)/2. Thus, the equation of the tangent line is:   y + (√2)/2 = -(3√2)/2 (x - π/4), or equivalently:   y = -(3√2)/2 (x - π/4) - (√2)/2. This completes the solution.

Answered by UpStudy AI and reviewed by a Professional Tutor

error msg
Explain
Simplify this solution

Mind Expander

To find the equation of the tangent line to the function \( y = \cos(3x) \) at the point \( \left( \frac{\pi}{4}, -\frac{\sqrt{2}}{2} \right) \), we first need to determine the derivative of the function, which represents the slope of the tangent line. The derivative is: \[ y' = -3\sin(3x). \] Now evaluate the derivative at \( x = \frac{\pi}{4} \): \[ y'\left( \frac{\pi}{4} \right) = -3\sin\left(3 \cdot \frac{\pi}{4}\right) = -3\sin\left(\frac{3\pi}{4}\right) = -3 \cdot \frac{\sqrt{2}}{2} = -\frac{3\sqrt{2}}{2}. \] Now that we have the slope, we can use the point-slope form of the line: \[ y - y_1 = m(x - x_1), \] where \( (x_1, y_1) = \left( \frac{\pi}{4}, -\frac{\sqrt{2}}{2} \right) \) and \( m = -\frac{3\sqrt{2}}{2} \). Substituting these values in: \[ y + \frac{\sqrt{2}}{2} = -\frac{3\sqrt{2}}{2}\left(x - \frac{\pi}{4}\right). \] This gives the equation of the tangent line at the point in question!

Try Premium now!
Try Premium and ask Thoth AI unlimited math questions now!
Maybe later Go Premium
Study can be a real struggle
Why not UpStudy it?
Select your plan below
Premium

You can enjoy

Start now
  • Step-by-step explanations
  • 24/7 expert live tutors
  • Unlimited number of questions
  • No interruptions
  • Full access to Answer and Solution
  • Full Access to PDF Chat, UpStudy Chat, Browsing Chat
Basic

Totally free but limited

  • Limited Solution
Welcome to UpStudy!
Please sign in to continue the Thoth AI Chat journey
Continue with Email
Or continue with
By clicking “Sign in”, you agree to our Terms of Use & Privacy Policy